2009
DOI: 10.1016/j.renene.2008.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Economic feasibility of solar-powered led roadway lighting

Abstract: The optical efficacy of light emitting diode (LED) has exceeded 72 lm/W in 2006. This implies that energy can be saved about 75%, as compared to mercury lamps widely used in roadway lighting. In some remote areas where the grid power cannot reach, independent solar-powered lighting using high-power LED provides a promising solution. However, the cost of solar photovoltaic device may cause the application of solar-powered LED roadway lighting to be not economically feasible. The present study investigates the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 2 publications
(2 reference statements)
0
32
0
2
Order By: Relevance
“…Por ejemplo, la luminaria LED de 200W, brinda los valores de luminancia e iluminación más altos en comparación con los otros sistemas de luminarias; sin embargo, el precio de esta luminaria es de aproximadamente USD 1,000 por lámpara (Wu et al, 2009). En el caso de la luminaria LED de 150W brinda valores de luminancia e iluminación inferiores a los obtenidos con la luminaria LED de 200W; no obstante, su precio es de aproximadamente USD 760 por lámpara (Tähkämö et al, 2016).…”
Section: Dialuxunclassified
“…Por ejemplo, la luminaria LED de 200W, brinda los valores de luminancia e iluminación más altos en comparación con los otros sistemas de luminarias; sin embargo, el precio de esta luminaria es de aproximadamente USD 1,000 por lámpara (Wu et al, 2009). En el caso de la luminaria LED de 150W brinda valores de luminancia e iluminación inferiores a los obtenidos con la luminaria LED de 200W; no obstante, su precio es de aproximadamente USD 760 por lámpara (Tähkämö et al, 2016).…”
Section: Dialuxunclassified
“…In recent years, due to the rapid development of high power LEDs, thermal management and heat dissipation become essential [19]. Therefore, heat dissipation is an important issue in highpower LED lighting technology [20].…”
Section: Multichip Power Leds and Heatmentioning
confidence: 99%
“…Wu et al [4] have presented and investigated the design of solar-powered LED roadway lighting using high power LED luminaries (100 W), and estimated the total cost of installations for a 10 km highway with two lanes. A comparison between LED lighting using solar power and grids, with traditional mercury lamps, regarding cost, found that 75% of energy can be saved by using LED lighting.…”
Section: Introductionmentioning
confidence: 99%